Challenging the Eurocentrism in volunteering. Issue 1 (2nd January 2023) - Polus, Reni; Carr, Neil; Walters, Trudie
ABSTRACT: Volunteering practices have largely drawn on theories based on Eurocentric conceptualizations. The dominant Eurocentric models of volunteering, as a significant leisure experience, have served to marginalize other definitions and practices. Thus, this paper argues that, while the Eurocentric conceptualization provides a useful framework to understand volunteering in different cultural contexts, it is critical to embrace the complexities and nuances that exist beyond this. Consequently, the paper presents a critical examination of the limitations of this dominant conceptualization of volunteering. In doing so, the paper challenges Eurocentrism domination in the studies of volunteerism and discourse and examines how volunteering can (and does) differ across cultural contexts, to varying degrees. Overall, this paper shows that volunteering is a more complex and nuanced concept than the dominant Eurocentric models depict. Consequently, this paper offers a potential springboard from which to critically examine potentially contested culturally driven meanings of leisure, of which volunteering is an integral component, empowering people to own their leisure rather than conform to Eurocentric definitions of leisure.